Long-Term Pulmonary Function and Quality of Life in Children After Acute Respiratory Distress Syndrome: A Feasibility Investigation. Issue 1 (January 2017) - Ward, Shan L.; Turpin, Autumn; Spicer, Aaron C.; Treadwell, Marsha J.; Church, Gwynne D.; Flori, Heidi R.
Abstract : Objectives: To determine the feasibility of pulmonary function and quality of life evaluations in children after acute respiratory distress syndrome. Design: A prospective follow-up feasibility study. Setting: A tertiary PICU. Patients: Children less than 18 years old with acute respiratory distress syndrome admitted between 2000 and 2005. Intervention: Pulmonary function testing and patient and parental quality of life surveys approximately 12-month after acute respiratory distress syndrome. Measurements and Main Results: One hundred eighty patients met acute respiratory distress syndrome criteria; 37 (20%) died, 90 (51%) declined participation, 28 (16%) consented but did not return, and 24 (13%) returned for follow-up visit. Twenty-three patients completed quality of life testing and 17 completed pulmonary functions. Clinical characteristics of those who returned were no different from those who did not except for age (median age, 4.9 vs 1.8 yr). One-third had mild to moderate pulmonary function deficits. Quality of life scores were marginal with general health perception, physical functioning, and behavior being areas of concern. These scores were lower than scores in children with chronic asthma. Parental quality of life assessments report lower scores in single-parent homes but no differences were noted by race or parental employment status. Conclusions: Valuable information may be discerned from acute respiratory distress syndrome patients who return for follow-up evaluation. In this pilot study, up to one-third of children with acute respiratory distress syndrome exhibit pulmonary function deficits and 12-month postillness quality of life scores are lower than in children with chronic asthma. Parental perceptions of postillness quality of life may be negatively impacted by socioeconomic constraints. Long-term follow of children with acute respiratory distress syndrome is feasible and bears further investigation. Abstract : Supplemental Digital Content is available in the text.